If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m(m + 6) = 72 Reorder the terms: m(6 + m) = 72 (6 * m + m * m) = 72 (6m + m2) = 72 Solving 6m + m2 = 72 Solving for variable 'm'. Reorder the terms: -72 + 6m + m2 = 72 + -72 Combine like terms: 72 + -72 = 0 -72 + 6m + m2 = 0 Factor a trinomial. (-12 + -1m)(6 + -1m) = 0Subproblem 1
Set the factor '(-12 + -1m)' equal to zero and attempt to solve: Simplifying -12 + -1m = 0 Solving -12 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -1m = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -1m = 0 + 12 -1m = 0 + 12 Combine like terms: 0 + 12 = 12 -1m = 12 Divide each side by '-1'. m = -12 Simplifying m = -12Subproblem 2
Set the factor '(6 + -1m)' equal to zero and attempt to solve: Simplifying 6 + -1m = 0 Solving 6 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1m = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1m = 0 + -6 -1m = 0 + -6 Combine like terms: 0 + -6 = -6 -1m = -6 Divide each side by '-1'. m = 6 Simplifying m = 6Solution
m = {-12, 6}
| 73+4x=-5x-134 | | y=390+60y | | 4x^2-16x=-15 | | 72+4x=-5x-134 | | 2(w^2)-9w=0 | | y=510+60y | | -40+-6= | | 5x-34=-2x+78 | | 21x-400=x | | 112=-41+9x | | 12(3x-4)=3(12x+6) | | y=590+.60y | | 2X-1=33+X | | 10-3x=58 | | 5*0-4y=-20 | | 4x-58=-x+27 | | 6+12m-2=7m+76-3m | | -80=-5x-30 | | -6x-10=32 | | x^4+10x^3+36x^2+56x+32=0 | | -2p+8=5-(9p+6) | | -12x=288 | | m(7+m)=78 | | -47+4x=34+7x | | 12x^2y-16x^2-18y+24=0 | | 150=-7x+5(-x+6) | | 10x^2+28x-96=0 | | 8c-5c-6c= | | 6*0-5y=-30 | | -x(x-8)+2(x+2)=x+9 | | -4x^2+3x-5=0 | | 0.18(18)+0.03x=0.09(12+x) |